Physiological and morphological effects of overproduction of membrane-bound ATP synthase in Escherichia coli K-12. - von Meyenburg, K (1984)
Effects of increased biosynthesis of the membrane-bound ATP synthase of Escherichia coli K-12 were analysed at the physiological and morphological level. Overproduction of the enzyme complex was achieved by molecular cloning of the structural genes into plasmid pBR322. A series of plasmids resulting in 2-fold, 4- to 5-fold and 10- to 12-fold overproduction, respectively, was constructed. The ATP synthase was calculated to represent 3%, 6-7% and 18-23%, respectively, of total protein in cells with these plasmids. In wild-type cells ATP synthase represents 1.5-2% of total protein equivalent to approximately 3000 enzyme complexes per average cell. While 2- or 4- to 5-fold wild-type levels of the ATP synthase had only minor effects it was found that 10- to 12-fold overproduction resulted in pronounced inhibition of cell division and growth and in formation of membrane cisterns and vesicles within the cells. Inclusion bodies, probably representing deposits of excess ATP synthase, were also observed in these cells.